(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The ethnomedicinal application of rare and endangered medicinal plants holds significant promise for both traditional healing practices and modern healthcare advancements. This comprehensive review explores the multifaceted dimensions of this practice, emphasizing its ethnobotanical, conservation, pharmacological, cultural, and policy-related aspects. Drawing upon indigenous knowledge and traditional practices, the study underscores the importance of documenting and preserving ethanomedicinal wisdom, particularly concerning rare and endangered plant species. Conservation efforts emerge as a critical concern, as dwindling plant populations necessitate both in situ and ex situ strategies to safeguard these invaluable resources. Pharmacological investigations reveal the bioactive compounds present in these plants, supporting their potential for drug development and therapeutic innovations. Case studies spotlight specific ethnomedicinal plant species, exemplifying the delicate balance between traditional uses and contemporary conservation imperatives. Cultural and ethical considerations emerge as pivotal aspects, necessitating collaborative research models that respect indigenous knowledge and uphold intellectual property rights. The dynamic interplay between traditional practices and global market trends presents opportunities for sustainable livelihoods while posing challenges in maintaining equitable benefit-sharing. The legal and policy landscape is examined in light of international conventions, national legislation, and the evolving frameworks governing the utilization and protection of ethnomedicinal resources. As ethnomedicinal practices transition from local traditions to global enterprises, a harmonious coalescence of traditional wisdom and modern scientific rigor emerges as essential. This chapter offers insights into the current landscape and future prospects of ethnomedicinal practices involving rare and endangered medicinal plants. It underscores the urgency of collaboration between various stakeholders, bridging the gap between traditional knowledge and contemporary science for the preservation of biodiversity and the promotion of holistic healthcare systems.